2013
DOI: 10.1049/iet-map.2011.0398
|View full text |Cite
|
Sign up to set email alerts
|

Low‐cost intelligent antenna with low profile and broad bandwidth

Abstract: In this study, a low‐cost intelligent antenna, which has a low profile, high gain and broad bandwidth, is presented. The proposed antenna is an extension of the conventional electronically steerable parasitic array radiator antenna. It consists of one short monopole and 12‐folded monopoles. The short monopole is placed in the centre and serves as the driven element and the 12‐folded monopoles serve as parasitic elements. The coupling between the driven and parasitic elements provides capacitive loading to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…Standard WSN devices with monopole antenna usually exhibit a very poor performance in multipath scenarios [8], and this can severely limit their operation. In contrast to monopoles, smart antennas [9][10][11][12] are able to dynamically control their radiation pattern as a function of direction. They can steer their main beam towards a desired signal while forming a null in the direction of an interference signal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard WSN devices with monopole antenna usually exhibit a very poor performance in multipath scenarios [8], and this can severely limit their operation. In contrast to monopoles, smart antennas [9][10][11][12] are able to dynamically control their radiation pattern as a function of direction. They can steer their main beam towards a desired signal while forming a null in the direction of an interference signal.…”
Section: Introductionmentioning
confidence: 99%
“…Also they are able to improve the network performance by enabling concurrent transmission in media access control (MAC) and routing layers. Studies of the use of pattern-steering smart antennas in WSNs [12][13][14][15][16] have demonstrated that they can provide benefits in increasing the wireless channel capacity while improving the communication quality. This has the potential to solve many of the challenges faced in WSN development.…”
Section: Introductionmentioning
confidence: 99%
“…For further size reduction, these traditional wideband methods with single working state are limited. Considering the limited space for antenna design for mobile handsets, reconfigurable technology [8][9][10][11][12][13][14][15][16][17] is a good candidate. By using the reconfigurable technology, the antenna can work in several states to obtain wide bandwidth with a reduced size.…”
Section: Introductionmentioning
confidence: 99%
“…By using the reconfigurable technology, the antenna can work in several states to obtain wide bandwidth with a reduced size. Commonly, the reconfigurability is achieved by RF MEMS switches [8][9][10][11], PIN diodes [11][12][13][14][15], and varactors [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation